Adaptation And Attenuation Of Very Virulent Infectious Bursal Disease Virus In Avian And Mammalian Cell Cultures For Vaccine Development - Khor, Sok Fang (2007)

(untitled)
Infectious bursal disease virus (IBDV) is an immunosuppressive virus causing infectious bursal disease (IBD) outbreaks since 1957. The economic impact of IBD is influenced by strain of virus, route of infection, intercurrent primary and secondary pathogens, and environmental management factors. Adaptation of IBDV to replicate in cell culture is associated with attenuation. Repeated passages of classical IBDV (cv IBDV) in avian primary cell culture, results in highly attenuated virus, which is commonly used as a live vaccine for many years. However, this cvIBDV vaccine does not provide full protection against very virulent IBDV (vvIBDV) infection. Field isolates particularly vvIBDV normally do not grow in cell cultures. It requires extensive passages and adaptation in chicken embryonated eggs before it can propagate in cell cultures. This study attempts to adapt and attenuate two local isolates of vvIBDV namely B0081 and UPM93273 in mammalian continuous cell line (Vero cell cultures) and avian primary cell line (Chicken embryo fibroblast, (CEF)). A newly modified method of adaptation and attenuation is introduced in this study. Both isolates were successfully adapted and attenuated in Vero cell cultures of 22 passages throughout the proposed modified method. Furthermore, through the modified method, both isolates can be adapted and propagated faster and easier in mammalian continuous cell cultures when compared with the conventional method. Passage 10 of isolate B0081 in Vero cell cultures using modified method, called B0081T was tested for pathogenicity in specific pathogen free (SPF) chickens. This study showed that UPM0081T caused sudden onset of 100% morbidity with no mortality during infection and the infected bursal recovered from the infection. Sequence comparison has also been carried out for nucleotides (nt) and deduced amino acids (aa) in hypervariable region (HVR) of VP2 of UPM0081T with the parental isolate B0081 in this study. As a result, the parental isolate B0081 revealed one mutation from G to A in UPM0081T at nucleotide position 850. This nucleotide substitution resulted in the substitution of Ala in the parental virus to Thr in the cell culture attenuated strains at residue 284. Amino acid residues Gln, Asp and Ala at position 253, 279 and 284 were conserved in most strains of high pathogenicity; and His, Asn and Thr were conserved in most of the cell culture attenuated strains of low pathogenicity in SPF chickens. The sequence of hypervariable region of VP2 of UPM0081T was deposited in GeneBank under accession number EF208038.In conclusion, IBDV B0081 was successfully adapted and propagated in mammalian continuous cell cultures by the proposed modified method. The adapted virus was named UPM0081T. It may serve as a seed virus in the production of local vaccine against vvIBDV infections, for the prevention and control of IBD in Malaysia.